Analisis Faktor Internal dan Eksternal pada Nilai Tanggung Jawab pada Peserta Didik Melalui Mata Pelajaran PPKn Kelas V di SD Negeri 2 Tambakrigadung - Salsabillah Salsabillah; Oriza Zativalen; Linaria Arofaul Usawatun Khasanah (Jurnal Tematik, 2025)
This study aims to analyze the internal and external factors that influence the responsibility values of fifth-grade students through the teaching of Pancasila and Civic Education (PPKn) at SD Negeri 2 Tambakrigadung, Lamongan. The research employed a descriptive qualitative approach, involving five students and two classroom teachers as subjects. Data collection techniques included observation, interviews, documentation, and questionnaires. The results showed that the students' sense of responsibility was categorized as fairly good, as reflected in behaviors such as completing assignments on time, cooperating in group work, and accepting consequences for their actions. The dominant internal factors included learning motivation, self-discipline, and diligence. Meanwhile, external factors such as teacher role modeling and the application of educational punishment contributed to the development of positive habits. PPKn learning proved effective in instilling character values, particularly responsibility. These findings can serve as a reference for educators in optimizing PPKn instruction as a means of strengthening students' character development.